Cultural adaptation of the mental health first aid guidelines for assisting a person at risk of suicide to China: a Delphi expert consensus study - Shurong Lu; Wenjing Li; Brian Oldenburg; Yan Wang; Anthony F. Jorm; Yanling He; Nicola J. Reavley (BMC Psychiatry, 2020)
Abstract Background Suicide is a significant public health concern in China and there is a need for evidence-based suicide prevention programs to assist people in the community who may be in a position to support those in their social networks who are at risk of suicide. English-language mental health first aid guidelines for this purpose have been developed. However, due to differences in culture, language and health systems, guidelines for English-speaking countries require cultural adaptation for use in China. Methods A Delphi expert consensus study was conducted among mainland Chinese panellists with a diverse range of expertise in suicide crisis intervention (n = 56). Using the mental health first aid guidelines used in English-speaking countries as a basis, a questionnaire containing 141 statements on how to help a person at risk of suicide was developed and translated. Panellists were asked to rate the importance of each item for inclusion in the Chinese guidelines. They were also encouraged to suggest any additional statements that were not included in the original questionnaire. Statements were accepted for inclusion in the adapted guidelines if they were endorsed by at least 80% of panellists as essential or important. Results Consensus was achieved after two survey rounds on 152 statements for inclusion in the adapted guidelines for China, with 141 adopted from the guidelines for English-speaking countries and 11 generated from the comments of panellists. Conclusions While the adapted guidelines were similar to the guidelines for English-speaking countries, they also incorporated actions specific to the Chinese context, including Chinese attitudes towards suicide, the role of families and friends and removal of the means of suicide. Further research is needed to investigate the use of the guidelines by the Chinese public and the implementation of Mental Health First Aid training in appropriate settings in China.